RAC3 more than a nuclear receptor coactivator: A key inhibitor of senescence that is down-regulated in aging - Fernández Larrosa, Pablo Nicolás (2015)
Receptor-associated coactivator 3 (RAC3) is a nuclear receptor coactivator usually overexpressed in tumors that exerts oncogenicfunctions in the cytoplasm and the nucleus. Although as part of its oncogenic actions it was previously identified as an inhibitor ofapoptosis and autophagy, its expression is required in order to preserve the pluripotency and embryonic stem cell self-renewal. Inthis work we investigated its role in cellular senescence. We found that RAC3 overexpression in the nontumoral HEK293 cellsinhibits the premature senescence induced by hydrogen peroxide or rapamycin. The mechanism involves not only the inhibition ofautophagy early induced by these stimuli in the pathway to senescence, but also the increase in levels and nuclear localization ofboth the cell cycle suppressors p53/p21 and the longevity promoters FOXO1A, FOXO3A and SIRT1. Furthermore, we found thatRAC3 overexpression is required in order to maintain the telomerase activity. In tumoral HeLa cells its activity was inhibited bydepletion of RAC3 inducing replicative senescence. Moreover, we demonstrated that in vivo, levels of RAC3 are downregulated inthe liver from aged as compared with young rats, whereas the levels of p21 are increased, correlating with the expected senescentcell contents in aged tissues. A similar downregulation of RAC3 was observed in the premature and replicative senescence ofhuman fetal WI-38 cells and premature senescence of hepatocyte HepG2 cell line. Taken together, all these results demonstratethat RAC3 is an inhibitor of senescence whose downregulation in aged individuals could be probably a tumor suppressormechanism, avoiding the clonal expansion of risky old cells having damaged DNA.